2012
DOI: 10.1016/j.molcel.2012.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Bim Inhibits Autophagy by Recruiting Beclin 1 to Microtubules

Abstract: Summary Bim is a proapoptotic BH3-only Bcl-2 family member. In response to death stimuli, Bim dissociates from the dynein light chain 1 (DYNLL1/LC8), where it is inactive, and can then initiate Bax/Bak-mediated mitochondria-dependent apoptosis. We found that Bim depletion increases autophagosome synthesis in cells and in vivo, and this effect is inhibited by overexpression of cell death-deficient Bim. Bim inhibits autophagy by interacting with Beclin 1, an autophagy regulator, and this interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 50 publications
5
153
0
Order By: Relevance
“…BCL2L11 is known to bridge the interaction between BECN1 and the dynein light chain LC8 and thus inhibits autophagy through targeting BECN1 to the cytoskeleton. 35 Nevertheless, phosphorylation of BCL2L11 abrogates binding of LC8 to BCL2L11, causing their disassociation and activation of autophagy. 35 We found that ER stress increased phosphorylation of BCL2L11, which conceivably contributed activation of autophagy by freeing BECN1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCL2L11 is known to bridge the interaction between BECN1 and the dynein light chain LC8 and thus inhibits autophagy through targeting BECN1 to the cytoskeleton. 35 Nevertheless, phosphorylation of BCL2L11 abrogates binding of LC8 to BCL2L11, causing their disassociation and activation of autophagy. 35 We found that ER stress increased phosphorylation of BCL2L11, which conceivably contributed activation of autophagy by freeing BECN1.…”
Section: Discussionmentioning
confidence: 99%
“…20,30,32 Activation of MAPK8/9 by ER stress also activates autophagy through phosphorylation of prosurvival BCL2 family proteins including BCL2 and BCL2L1/BIM thus dissociating them from BECN1/Beclin 1 that plays a critical part in initiation of autophagy flux. [33][34][35][36] Similarly, the other prosurvival protein MCL1 can also bind to BECN1 and disruption of the association triggers autophagy. 37,38 It seems therefore that ER stress may activate autophagy through varying mechanisms depending on cell types and stimuli in question.…”
Section: Ripk1 (Receptor [Tnfrsf]mentioning
confidence: 99%
See 1 more Smart Citation
“…37 This interaction of Bim-EL and LC8 has been more recently shown to also involve binding to Beclin-1, a critical mediator of autophagy. 38 The formation of this Bim-EL-LC8-Beclin-1 complex has been proposed to block the pro-apoptotic activity of Bim-EL by sequestering it away from the mitochondria. Given these data, we hypothesized that ERK-mediated phosphorylation of Bim-EL at S59 in IBC cells could block anoikis by promoting the formation of the Bim-EL-LC8-Beclin-1 complex.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the interaction of Beclin-1 with LC8 and Bim-EL has been shown to prevent Beclin-1 from initiating autophagosome formation, 38 it seems reasonable to speculate that ECMdetached IBC cells are defective in autophagy in addition to anoikis. This presents a unique problem for these cells, as autophagy has previously been shown to be critical for the survival of ECM-detached cells, 46,47 presumably to facilitate nutrient consumption.…”
Section: Discussionmentioning
confidence: 99%